Comment maintenir l'action conjointe dans les enseignements universitaires en distanciel ? - Philippe Clauzard (Université de Provence, 2022)
This article focuses on distance teaching-learning activities at the university and wonders how to maintain joint action there. It reports a questionnaire distributed to students and an analysis according to the criteria of the theory of joint action in didactics in order to question how to rethink a co-activity of "distance" training, where the physical absence of face-to-face teaching can be compensated by a renewed cognitive presence within the digital space of communication of new knowledge. However, the difficulty lies in the contradictory interactions and collaborations within a didactic system whose criteria must be rethought.